AKTIVASI OPTIMASI INSTAGRAM BUSINESS ALBANNA.ID DALAM MEMBANGUN BRAND FASHION MUSLIM DI MASYARAKAT KABUPATEN KARANGANYAR - Dani, Jeratallah Aram; Syaifudin, Makmun; Syaifullah, Jahid (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2024)
Instagram marketing is a marketing strategy that uses the social media platform Instagram as a tool to promote businesses, brands and products to audiences. The focus of this research is to reveal Albanna.id's promotional strategy using the social media Instagram. With a case study approach, this research will reveal the steps taken by albanna.id, as the object of research. Primary data was obtained through interviews with the owner and documentation of albanna.id Instagram displays in promotional and sales activities. Secondary data is obtained through observations and observations as well as additional information from the albanna.id admin in each posting plan that has been created and determined with the owner. The results of this research are, albanna.id in making sales on Instagram social media uses the features provided by Instagram, the features used are nametag, pin feed, Instagram highlight, Instagram live, music in feed, insight, auto reply , and hashtags. Keywords: Instagram, Optimization, Promotion